Studi Fenomenologi : Pengalaman Keyakinan Diri Terhadap Penyembuhan Covid-19 - Arizki Rahman Hakim; Ichsan Budiharto; Muhammad Ali Maulana (State University of Gorontalo, 2023)
The Covid-19 pandemic requires every exposed community to selfisolate, including nursing students. When required to self-isolate, nursing students have many stressors that affect their self-confidence (Self Efficacy). Objective to explore the self-efficacy experience of nursing students at X University during the self-isolation process. Using a qualitative design with a phenomenological approach as many as six participants with the snowball sampling method. Collecting data using a semi-structured interview method for 10-20 minutes using thematic analysis. There were four themes identified from the thematic analysis, namely (1) exposure to Corona Virus Disease (Covid-19) which explained how participants were exposed to Covid-19, when participants were Covid-19, and the signs and symptoms that participants felt; (2) self efficacy enhancement strategies in the form of fulfilling basic needs, fulfilling information needs, and coping mechanisms; (3) self efficacy factors, namely the support of the surrounding environment, expectations, motivation, and level of knowledge; and (4) Barriers to increasing self efficacy in the form of changes in physical condition, stress load, and interaction and communication. The description of the experience of nursing students' beliefs when doing independent isolation is influenced by several aspects including exposure to Covid-19, improvement strategies, self efficacy, self efficacy factors, and barriers to increasing self efficacy.